On features of the radiation from pulsed discharges initiated by thick wires in water - Fedorovich, O.A.; Voitenko, L.M. (Вопросы атомной науки и техники, 2015)
The investigation results on the distribution of the plasma channel radiance intensity in the visible spectral region are reported. The pulsed discharge in water is initiated by the Tungsten wire (Ø 300 μm) explosion under initial battery voltage of 20 kV. The plasma channel radiance intensity does not correlate with the power contribution into the plasma. The energy contribution ceases at 20 μs, and the maximum radiation of the continuous spectrum is observed at 80 μs. The radiation intensity is practically constant between 50 and 120°up to the basic state. It is not succeeded to record the intensity (Тn ≤ 6·10³ К) in the interval to 20 μs. The dynamics in time of the absorption line spectrum in the region between 490…560 nm, explaining the radiation intensity increase with time, is investigated. The visible radiation region comprises a wave length band corresponding to the plasma frequency in the channel. In the course of time, the plasma frequency band displaces into the red spectral region and the radiation intensity in the violet region increases to the values corresponding to Т = 2·10⁴ К. The radiation reflection from the channel boundary at the plasma frequency takes place. The time dependence of the pressure obtained from the experimental hydrodynamic calculation results has been compared with the adiabatic curve. A significant difference between results is evident. The same calculation for the temperature change shows that at the initial discharge stage T= 3·10⁴ К should be reached. The radiation spectrum dynamics in the region between 620 and 700 nm is shown. In the Нα line region (656.3 nm) neither the absorption line nor the radiation line are observed in the spectrum up to 83 μm.